PENGARUH PASAR MODAL SYARIAH TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Retno Indri Yustika; Meli Repi Yani; Novita Sari (Program Studi Ekonomi Syariah, 2024)
This research aims to examine the influence of the Islamic capital market on Indonesian state income over a period of 6 years and 6 months, starting from 2019 to 2024. This type of research is quantitative research, using time series data from monthly secondary data obtained from website reports Financial Services Authority (OJK) and Central Statistics Agency (BPS). The data management technique uses classical assumption and hypothesis testing with the help of E-views 12 software. Meanwhile, the variable studied is sharia shares which act as an independent variable, while state income acts as a dependent variable. The analytical method used in this research is simple regression analysis, with research results showing that sharia shares play an important role in influencing Indonesian state income.